Pemanfaatan Sumber Daya Lokal Selada Air Melalui Pelatihan Pembuatan Crackers Selada Sebagai Alternatif Kuliner Berkelanjutan - Bayu Bagas Hapsoro; Ayu Agustyarini, Putri; Jazilatun Nafisah (Jurnal Bina Desa, 2025)
Optimal use of local resources is one of the keys to creating sustainable culinary innovation. This research aims to improve the skills of the people of Karangsari Village, Pulosari District, Pemalang Regency in processing watercress, a local commodity that is abundant in the area, into culinary products that have high selling value, namely watercress crackers. The training on making watercress crackers carried out by the UNNES GIAT 9 team used the method of transferring knowledge and skills directly to the women of RT 17 in Nusa Hamlet. The results of this training show an increase in participants' knowledge and skills in processing watercress into innovative and sustainable culinary products. Another positive impact is the creation of home business opportunities for local communities, which supports local economic development and the preservation of culinary culture. Thus, this training succeeded in encouraging the use of local resources as a solution in creating sustainable culinary alternatives that can compete in the global market.